Phosphite mediated molecular editing via switch to meta-C-H alkylation of isoquinolines: emergence of a distinct photochemical [1,3] N to C rearrangement - Rani, Soniya; Ray, Anuj Kumar; Dewangan, Devendra Kumar; Patil, Nita Aruna Ramchandra; Aarthika, M.; Paul, Ankan; Maity, Pradip (Chemical Science, 2025)
The isoquinoline core is present in one of the largest subsets of bioactive natural products. The multifunctional isoquinoline core exerts diverse bioactivity, resulting in the development of numerous isoquinoline-based drugs and molecules that are currently under clinical trials. We developed a new approach for phosphite-mediated [1,2] alkyl migration for an overall ortho-C-H alkylation via N-alkylation of isoquinoline. Tuning the phosphite-mediated protocol to switch the site selectivity would expedite direct and diverse multi-C-H bond functionalization. We report a new approach starting with a simple N-alkylation of isoquinoline with sterically and electronically diverse alkyl bromides for their phosphite-mediated photochemical [1,3] N to C rearrangement followed by a rearomatization sequence that leads to meta-C-H (C4) alkylation. Combined experimental and computational studies unveiled the emergence of an unprecedented C-N bond cleavage pathway from the singlet excited state of the enamine-type intermediate. Our radical bond-cleavage pathway favors substituted alkyl group migration that complements the recently successful meta-alkylation methods with smaller and more reactive electrophiles. This switch in site selectivity via tuning the phosphite-mediated protocol resulted in sequential C-H difunctionalization of isoquinoline including regiodivergent ortho, meta-dialkylations of isoquinolines.

Mild and site-selective nucleophilic C-H functionalization of pyridines via its stable N-alkylated salts - Baral, Nilofar; Saikia, Pinku; Molla, Sabir Ali; Dewangan, Devendra Kumar; Maity, Pradip (Journal of the American Chemical Society, 2026)
Direct, site-selective C-H functionalization of pyridines offers an efficient approach to both streamlined synthesis and late-stage modification of bioactive and functional molecules. Existing approaches to direct nucleophilic substitution typically rely on highly reactive nitrogen-activating groups, which limit nucleophile scope and functional group tolerance and often suffer from poor site selectivity. Although milder activating groups address some of these limitations, they generally require additional installation and removal steps. Herein, we report a mild and general strategy employing designed alkyl halide activators that enables one-pot, site-selective functionalization of pyridines with synthetically valuable yet challenging nucleophiles. This strategy allows, for the first time, direct pyridine functionalization with a broad range of phosphites and amines, in addition to methoxide and cyanide. The mild and redox-neutral reaction conditions are particularly well suited for late-stage functionalization (LSF) of pharmaceutically relevant molecules, enabling site-selective modification with both phosphites and amines. The rational design of the alkyl halide activators, together with careful analysis of side-product formation, reveals the delicate balance required for success with electronically diverse nucleophiles and suggests broader applicability of this C-H functionalization strategy.